'Only one can rule the night': Fairs and music in post-1945 Britain. (24th November 2017) - Trowell, Ian
Abstract : This article charts and examines the relationship between popular music and the British travelling fairground in the post-war years. I set out a historical trajectory of the importance of sound and noise within the fairground, and examine how music in the post-war years emerged as an important aspect of this wider soundscape. The complex spatial characteristics of the fairground are considered as fragmented zones with 'interiors-within-interiors' forming to facilitate certain music and sounds. This progresses to encompass and engage the subcultural explosion in British society. The fairground becomes a complex mode of musical consumption, enhancing the sound through somatic engagement and providing a temporary space for subcultures to flourish. I draw on historical materials, archival evidence and gathered testimony to look at the 1950s period of new music, then plot a course to the current phase of dance music and club culture.